A point mutation in the gene for asparagine-linked glycosylation 10B (Alg10b) causes nonsyndromic hearing impairment in mice (Mus musculus). - Frank J Probst; Rebecca R Corrigan; Daniela Del Gaudio; Andrew P Salinger; Isabel Lorenzo; Simon S Gao; Ilene Chiu; Anping Xia; John S Oghalai; Monica J Justice (PLoS ONE, 2013)
The study of mouse hearing impairment mutants has led to the identification of a number of human hearing impairment genes and has greatly furthered our understanding of the physiology of hearing. The novel mouse mutant neurological/sensory 5 (nse5) demonstrates a significantly reduced or absent startle response to sound and is therefore a potential murine model of human hearing impairment. Genetic analysis of 500 intercross progeny localized the mutant locus to a 524 kilobase (kb) interval on mouse chromosome 15. A missense mutation in a highly-conserved amino acid was found in the asparagine-linked glycosylation 10B gene (Alg10b), which is within the critical interval for the nse5 mutation. A 20.4 kb transgene containing a wildtype copy of the Alg10b gene rescued the mutant phenotype in nse5/nse5 homozygous animals, confirming that the mutation in Alg10b is responsible for the nse5/nse5 mutant phenotype. Homozygous nse5/nse5 mutants had abnormal auditory brainstem responses (ABRs), distortion product otoacoustic emissions (DPOAEs), and cochlear microphonics (CMs). Endocochlear potentials (EPs), on the other hand, were normal. ABRs and DPOAEs also confirmed the rescue of the mutant nse5/nse5 phenotype by the wildtype Alg10b transgene. These results suggested a defect in the outer hair cells of mutant animals, which was confirmed by histologic analysis. This is the first report of mutation in a gene involved in the asparagine (N)-linked glycosylation pathway causing nonsyndromic hearing impairment, and it suggests that the hearing apparatus, and the outer hair cells in particular, are exquisitely sensitive to perturbations of the N-linked glycosylation pathway.